2017
DOI: 10.1177/0741932516685407
|View full text |Cite
|
Sign up to set email alerts
|

Participant Diversity in Special Education Research: Parent-Implemented Behavior Interventions for Children With Autism

Abstract: Evidence-based practices for children with disabilities have empirical support for their effectiveness; however, the demographics of participants making up the evidence base are generally unknown, leaving generalizability of the evidence unclear. This study presents a systematic literature review of participant racial and socioeconomic demographics in one area of special education research, parent-implemented interventions for reducing problem behavior in children with autism, to examine demographic reporting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 62 publications
(86 reference statements)
5
23
3
Order By: Relevance
“…Fewer than half of the studies (49.1%) included in the review reported the race/ethnicity of children, which is a higher percentage than other recent literature reviews where race/ethnicity was reported for 28% (Pierce et al, 2014), 36% (Severini et al, 2018), and 39% (Robertson et al, 2017) of the articles. African American/Black children were significantly overrepresented in the studies included in this literature review.…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…Fewer than half of the studies (49.1%) included in the review reported the race/ethnicity of children, which is a higher percentage than other recent literature reviews where race/ethnicity was reported for 28% (Pierce et al, 2014), 36% (Severini et al, 2018), and 39% (Robertson et al, 2017) of the articles. African American/Black children were significantly overrepresented in the studies included in this literature review.…”
Section: Discussionmentioning
confidence: 75%
“…This mirrors the findings in the very recent review of school-based problem behavior interventions for older students with ASD (Severini et al, 2018). All other intervention-related literature reviews have previously found that White children were overrepresented in studies (e.g., Pierce et al, 2014; Robertson et al, 2017; West et al, 2016). The Severini and colleagues’ (2018) review and this review were the first to specifically focus on interventions for challenging behavior in school settings.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations